Unusual case of a leiomyoma in the space of Retzius mimicking broad ligament fibroid. Issue 3 (1st March 2023) - Goyal, Lajya Devi; Goyal, Suresh; Garg, Priyanka; Mahajan, Garima
Abstract : This case report will discuss an interesting case of a patient who presented with pain in the lower abdomen of 2-month duration. Clinical examination and imaging findings were suggestive of a broad ligament fibroid. However, intraoperatively, the mass was found to be present in the space of Retzius, which is an extremely rare location for such a pathology. The access to the tumour was very challenging. Successful surgical excision was done with the help of a multidisciplinary team involving a gynaecologist, a urologist and an anaesthetist. Histopathology reported it to be benign leiomyoma. Postoperatively, the patient made an uneventful recovery.